Computational studies of different tail rotors characteristics under «spontaneous» rotation of helicopter - Krymsky, V.S.; Animitsa, V.A.; Leontiev, V.A. (My University, 2015)
In this work, the factors that make the helicopter to enter into the «spontaneous» rotation were computationally analyzed. The characteristics have been calculated of different tail rotors under rotation conditions with the angular velocities ?? =0 ?/sec, ?? =30 ?/sec, ?? =60 ?/sec and ?? =120 ?/sec to the left side when hovering without the ground effect. The computational studies have been carried out by using the helicopter mathematical model, developed in TsAGI. A relationship between the tail rotor relative thrust coefficient and the angular velocities ??/?(??) has been obtained.
Keywords: Dynamics